A rhetoric of remnants : idiots, half-wits, and other state-sponsored inventions - Stuckey, Zosha, 1971- (SUNY Press, 2014)
In the nineteenth century, language, rather than biology, created what we think of as disability. Much of the rhetorical nature of "idiocy," and even intelligence itself, can be traced to the period when the New York State Asylum for Idiots in Syracuse first opened in 1854--memorialized today as the first public school for people considered "feeble-minded" or "idiotic." The asylum-school pupil is a monumental example of how education attempts to mold and rehabilitate one's being. Zosha Stuckey demonstrates how all education is in some way complicit in the urge to normalize.The broad, unstable, and cross-cultural category of "people with disabilities" endures an interesting relationship with rhetoric, education, speaking, and writing. Stuckey demystifies some of that relationship which requires new modes of inquiry and new ways of thinking, and she calls into question many of the assumptions about embodied differences as they relate to pedagogy, history, and public participation.